Rights and responsibilities in rural South Africa : gender, personhood, and the crisis of meaning - Rice, Kathleen (Indiana University Press, 2023)
"Rights and Responsibilities in Rural South Africa examines the gendered and generational conflicts surrounding social change in South Africa's rural Eastern Cape roughly twenty years after the end of Apartheid. In post-Aparatheid South Africa, rights-based public discourse and state practices promote liberal, autonomous, and egalitarian notions of personhood, yet widespread unemployment and poverty demand that people rely closely on one another and forge relationships that disrupt the gendered and generational hierarchies framed as traditional and culturally authentic. Kathleen Rice examines the ways these tensions and restructurings lead to uncertainties about how South Africans should live together in their daily lives, with particular implications for understanding and responding to widespread gendered and sexual conflict and violence. Focusing particularly on the women of the village of Mhlambini, Rights and Responsibilities in Rural South Africa offers compelling portraits of how they experience and navigate widespread social and economic change and presents their experiences as a way of understanding how people navigate the moral ambiguities of contemporary South African life"--